Foreign Cry1Ab/c Delays Flowering in Insect-Resistant Transgenic Rice via Interaction With Hd3a Florigen - Fu, Jianmei; Liu, Guoqiang; Liu, Biao (Frontiers in Plant Science, 2021)
Genetic modifications in rice, which resulted in insect resistance, have been highly efficacious. However, they have also induced undesirable secondary phenotypes, such as delayed flowering. The molecular mechanisms associated with these unwanted effects remain unclear. Here, we showed that the flowering time for insect-resistant transgenic cry1Ab/c rice Huahui-1 (HH1) was delayed, compared with that for the parental rice Minghui-63 (MH63), cultivated on farmland and saline–alkaline soils. In contrast, the insect-resistant transgenic cry1C^* rice cultivars T1C-19 and MH63 had similar flowering times under the same conditions. We quantified the following: the expression of five major flowering genes in HH1, T1C-19, and MH63; florigen Hd3a protein expression levels in HH1 and MH63; interactions between Cry1Ab/c and the five main flowering proteins; and the effects of E3s ubiquitin ligase-mediated Cry1Ab/c expression on florigen Hd3a. Hd3a transcription was significantly lower in HH1 but not in T1C-19, compared with that in MH63. The results of yeast two-hybrid, complementary bimolecular fluorescence, and co-immunoprecipitation assays revealed that florigen Hd3a interacted with the exogenous Cry1Ab/c expressed in HH1 and not the exogenous Cry1C^* expressed in T1C-19. When Cry1Ab/c, Hd3a, and E3s fusion proteins were transiently co-expressed in tobacco cells, the Hd3a expression level was significantly lower than the level of Cry1Ab/c and Hd3a co-expression. Thus, the downregulation of Hd3a expression and the interaction between Cry1Ab/c and Hd3a interfere with Hd3a protein expression and might cooperatively delay HH1 flowering time. To the best of our knowledge, this study is the first to explain the delay in flowering time in insect-resistant transgenic rice, mediated by interactions between exogenous and endogenous proteins. This information might help elucidate the molecular mechanisms associated with these unwanted phenotypes effects and improve the process of biosafety assessment of transgenic rice.